Semiological differences between children and adults with temporal lobe epilepsy: a video-EEG based multivariate analysis - Mei, Aoxue; Xu, Ke; Gong, Mingkun; Fu, Cong; Bo, Yujie; Qiao, Jiao; Li, Tianfu; Wang, Mengyang; Wang, Xiongfei; Zhou, Jian; Guan, Yuguang; Luan, Guoming (Frontiers in Neurology, 2025)
ObjectiveThis study investigated the differences in semiological characteristics of temporal lobe epilepsy (TLE) between children and adult populations, specifically examining the impact of age on these manifestations. Using multivariate analysis, this study assessed the influence of age on TLE clinical manifestations, including seizure complexity, while controlling for etiology and lesion location.MethodsThis study retrospectively analyzed clinical data from patients who underwent anterior temporal lobectomy (ATL) and achieved seizure-free at Sanbo Brain Hospital. Semiological features were analyzed using video-electroencephalogram (video-EEG) recordings. Following descriptive analysis of clinical characteristics and seizure symptom differences between children and adult cohorts, univariate and multivariate logistic regression analyses were performed to evaluate associations between clinical variables and specific seizure components.ResultsA total of 176 patients (39 children and 137 adults) who underwent ATL and achieved seizure-free status met the inclusion criteria for this study. Significant differences were observed between children and adults in the incidence of: auras (p = 0.023), motor seizures (p = 0.002), clonic seizures (p = 0.002), focal to bilateral tonic–clonic seizures (p = 0.028), and lateralizing signs (p = 0.038). The incidence of automotor seizures (OR = 1.05, 95% CI 1.00–1.09, p = 0.039) and clonic seizures (OR = 1.06, 95% CI 1.01–1.12, p = 0.039) showed a positive correlation with increasing age.SignificanceThis study demonstrates significant age-dependent differences in semiological manifestations of TLE, suggesting that age-related neurodevelopmental changes underlie distinct seizure patterns. These findings support age-specific treatment strategies, as age affects TLE seizure patterns and clinical management decisions.